2021
DOI: 10.1111/jsr.13529
|View full text |Cite
|
Sign up to set email alerts
|

The impact of self‐selected short sleep on monetary risk taking

Abstract: Summary Risky choice has been widely studied in experimental settings, but there is a paucity of research examining the effects of self‐selected sleep schedules on risky choices. The current study examined incentivised risky choices of 100 young, healthy adults whose self‐selected (at‐home) sleep schedules were tracked via actigraphy for 1 week prior to decision making. Average nightly sleep was 6.43 h/night. On each trial of the decision task, individuals chose between two monetary gambles, with separate bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
4
1
Order By: Relevance
“…It also may suggest that less efficient compensatory strategies were used to perform the task. On the other hand, this result suggested that participants were less risky for both gains and losses after TSD, which is not entirely consistent with previous studies (Dickinson et al, 2022;McKenna et al, 2007). For example, there was a relative decrease in risk perception after TSD, which was manifested by increased sensitivity to reward and decreased sensitivity to risk (Banks et al, 2004;Harrison & Horne, 1998).…”
Section: Tsd Attenuates Neural Responses To Outcomes During Risk-takingcontrasting
confidence: 57%
See 1 more Smart Citation
“…It also may suggest that less efficient compensatory strategies were used to perform the task. On the other hand, this result suggested that participants were less risky for both gains and losses after TSD, which is not entirely consistent with previous studies (Dickinson et al, 2022;McKenna et al, 2007). For example, there was a relative decrease in risk perception after TSD, which was manifested by increased sensitivity to reward and decreased sensitivity to risk (Banks et al, 2004;Harrison & Horne, 1998).…”
Section: Tsd Attenuates Neural Responses To Outcomes During Risk-takingcontrasting
confidence: 57%
“…For example, there was a relative decrease in risk perception after TSD, which was manifested by increased sensitivity to reward and decreased sensitivity to risk (Banks et al., 2004; Harrison & Horne, 1998). Another study explored the impact of short sleep on monetary risk‐taking in more naturalistic settings and found that sleep variability increased risk‐taking behavior in the loss condition, which indicates that risk‐taking decisions may relate more to sleep efficiency variability than overall sleep duration or quality in naturalistic settings (Dickinson et al., 2022). The observed differences in task performance across studies could be due to the use of different paradigms, different risk settings, or different sleep parameters.…”
Section: Discussionmentioning
confidence: 99%
“…As negative emotions tend to increase during sleep deprivation (Killgore et al, 2008) or following poor quality sleep (Baglioni et al, 2010;Tkachenko et al, 2014), this lack of emotional regulatory capacity could exacerbate existing mental pain and thoughts of suicide for some individuals (Verrocchio et al, 2016). Second, consistent with the well-known role of the prefrontal cortex in higher order executive functioning and cognition, sleep deprivation has been shown to impair critical aspects of cognitive processing, including decisionmaking and risk propensity (Killgore et al, 2006;Dickinson et al, 2021), cognitive flexibility (Honn et al, 2019), as well as constructive thinking and emotional intelligence (Killgore et al, 2008). Deficits in many of these capacities have also been reported among individuals with chronic sleep disturbances (Cheng et al, 2017;Ballesio et al, 2019;Killgore et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Sleep loss has been shown to reduce positive mood state (Grezes et al, 2021 ; Stenson et al, 2021 ), degrade emotional intelligence (Killgore et al, 2008 , 2021 ), increase feelings of persecution (Kahn-Greene et al, 2007 ), and reduce frustration tolerance (Kahn-Greene et al, 2006 ), all of which can influence an individual’s outlook. Without sufficient restorative sleep, people make poorer decisions and take more risks under certain conditions (Killgore et al, 2006 ; Dickinson et al, 2021 ), particularly when relying on emotional valuation cues (Whitney et al, 2015 ). Mechanistically, many of these changes appear to be due to alterations in functional activity and neural communication throughout the brain produced by sleep deprivation (Venkatraman et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dickinson et al (2022) looked at the question whether self‐selected short sleep has an impact on monetary risk taking. To operationalize monetary risk taking people could choose between two monetary gambles, either aiming to “maximize gains” or to “minimize losses”.…”
mentioning
confidence: 99%